ДОСЛІДЖЕННЯ РІВНІВ СФОРМОВАНОСТІ ІНТЕЛЕКТУАЛЬНИХ УМІНЬ СТАРШОКЛАСНИКІВ (Педагогіка вищої та середньої школи, 2007)
In article results of an experimental research of levels of formation intellectual skills logically to operate with a teaching material at learning senior classes of secondaiy school are submitted.